2022
DOI: 10.3389/fneur.2022.814405
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Multimodal Neuromonitoring in Non-Critically Ill Hospitalized Adult Patients With COVID-19: A Systematic Review and Meta-Analysis

Abstract: IntroductionNeurological complications are frequent in patients with coronavirus disease-2019 (COVID-19). The use of non-invasive neuromonitoring in subjects without primary brain injury but with potential neurological derangement is gaining attention outside the intensive care unit (ICU). This systematic review and meta-analysis investigates the use of non-invasive multimodal neuromonitoring of the brain in non-critically ill patients with COVID-19 outside the ICU and quantifies the prevalence of abnormal neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…In a recent meta-analysis, the pooled prevalence of slow background abnormalities (theta and delta) in patients outside intensive care units (ICU) was 0.92 (95%CI 0.83–1.01, I 2 = 68.81%). The pooled prevalence of abnormal background in non-ICU patients was 0.95 (95%CI 0.88–1.09, I 2 = 44.98%) [ 20 ]. Diffuse slowing is the most frequent pattern also among our patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent meta-analysis, the pooled prevalence of slow background abnormalities (theta and delta) in patients outside intensive care units (ICU) was 0.92 (95%CI 0.83–1.01, I 2 = 68.81%). The pooled prevalence of abnormal background in non-ICU patients was 0.95 (95%CI 0.88–1.09, I 2 = 44.98%) [ 20 ]. Diffuse slowing is the most frequent pattern also among our patients.…”
Section: Discussionmentioning
confidence: 99%
“…The most common finding was the presence of abnormal background activity, followed by slow background, rhythmic and periodic discharges, and electroencephalographic seizures. This may be explained by various factors: (1) patients with COVID-19 might be at higher risk of hypoxic and metabolic changes responsible for encephalopathy; (2) after the virus enters the cells, a strong inflammatory response followed by cytokine storms may alter cerebral permeability and hemodynamic, thus favouring encephalopathy and multiple organ failure with potential for EEG alterations; (3) seizures, although a prevalence comparable to the non-COVID-19 population may be indicative of new neurological complications [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…NIRS has been evaluated to assess cerebral perfusion and autoregulation after cardiac arrest and detect episodes of cerebral desaturation showing a correlation between its values and severity of illness and with variable association between rSO 2 value and outcome [41,42]. Similarly, NIRS has shown to be useful to assess episodes of cerebral desaturation in patients with acute distress respiratory syndrome and COVID-19 during respiratory manipulations and the use of respiratory rescue therapies [7,[43][44][45][46], as well as in septic patients where cerebral desaturations were found to be predictors of neurological sequelae [47,48].…”
Section: Emergency Department and Intensive Care Unitmentioning
confidence: 99%
“…Among these, severe respiratory failure with or without extracorporeal membrane oxygenation (ECMO) [3,4], trauma, cardiac arrest, liver failure, intra-arterial thrombolysis during endovascular treatment [5,6], and sepsis are among the conditions where despite the absence of a primary cerebral damage, neurological complications are common and can affect patients' outcome [1]. The benefits of non invasive methods include safety, availability, and the provision of repeatable continuous data at the bedside, therefore helping clinicians detecting deterioration in neurologic function and earlier intervention [7].…”
Section: Introductionmentioning
confidence: 99%
“…Sedatives and anesthetics may impact patients' spontaneous breathing and MV duration. During the pandemic, metanalyses suggested that neuromonitoring patients with C-ARDS can be useful to guide sedation and detect those at risk of neurological complications ( 7 , 8 ). Tobar et al in a randomized double-blind trial, found that the use of a multiparameter electroencephalogram (EEG) protocol to guide sedation in C-ARDS as compared to no-EEG monitoring did not increase 30-day ventilator-free days, but reduced propofol administration and deeper sedation 5 days after randomization.…”
Section: Introductionmentioning
confidence: 99%